A Rare Presentation of Transfusional Hemochromatosis: Hypogonadotropic Hypogonadism - Rifki Ucler; Erdal Kara; Murat Atmaca; Sehmus Olmez; Murat Alay; Yaren Dirik; Aydin Bora (Case Reports in Endocrinology)
Hemochromatosis is a disease caused by extraordinary iron deposition in parenchymal cells leading to cellular damage and organ dysfunction. β-thalassemia major is one of the causes of secondary hemochromatosis due to regular transfusional treatment for maintaining adequate levels of hemoglobin. Hypogonadism is one of the potential complications of hemochromatosis, usually seen in patients with a severe iron overload, and it shows an association with diabetes and cirrhosis in adult patients. We describe a patient with mild transfusional hemochromatosis due to β-thalassemia major, presenting with central hypogonadism in the absence of cirrhosis or diabetes. Our case showed an atypical presentation with hypogonadotropic hypogonadism without severe hyperferritinemia, cirrhosis, or diabetes. With this case, we aim to raise awareness of hypogonadotropic hypogonadism in patients with intensive transfused thalassemia major even if not severe hemochromatosis so that hypogonadism related complications, such as osteoporosis, anergia, weakness, sexual dysfunction, and infertility, could be more effectively managed in these patients.